Effect of intrathecal dexmedetomidine on preventing shivering in cesarean section after spinal anesthesia: a meta-analysis and trial sequential analysis - Miao S; Shi M; Zou L; Wang G (Dove Medical Press, 2018)
Shuai Miao,* Mengzhu Shi,* Lan Zou, Guanglei Wang Department of Anesthesiology, The Affiliated Hospital of XuZhou Medical University, XuZhou, JiangSu, China *These authors contributed equally to this work Objective: Intrathecal dexmedetomidine (DEX) has been used to prevent shivering in patients undergoing cesarean section. The aim of this meta-analysis was to evaluate whether intrathecal DEX could prevent shivering in cesarean section after spinal anesthesia.Methods: We searched PubMed, Embase, Web of Science, and the Cochrane Library for randomized controlled trials (RCTs) comparing intrathecal DEX in cesarean section after spinal anesthesia with placebo and reporting on shivering, postoperative nausea and vomiting (PONV), hypotension, and bradycardia. Trial sequential analysis (TSA) was also carried out for RCTs comparing DEX with placebo. This meta-analysis has been registered on PROSPERO, and the registration number is CRD42017071640.Results: Six randomized clinical trials comparing 360 patients were included in this study. Compared with placebo, intrathecal DEX significantly reduced the incidence of shivering (risk ratio [RR]=0.40; 95% CI [0.26, 0.62]; P<0.0001). No significant difference was found in the incidence of PONV (RR=1.34; 95% CI [0.82, 2.18]; P=0.24), hypotension (RR=1.09; 95% CI [0.84, 1.42]; P=0.50), or bradycardia (RR=1.55; 95% CI [0.54, 4.42]; P=0.42). However, no firm conclusions can be made based on the results of all outcomes according to the TSA.Conclusion: This meta-analysis found that intrathecal DEX could prevent shivering in cesarean section after spinal anesthesia and did not induce PONV, hypotension, or bradycardia. However, firm conclusions cannot be made until more studies are conducted. Keywords: dexmedetomidine, cesarean section, spinal anesthesia, meta-analysis, trial sequential analysis, adverse effect